Feature inheritance, vP phases and the information structure of small clauses - Ángel L. Jiménez-Fernández; Vassilios Spyropoulos (Studia Linguistica, 2013)
In this paper we explore the interaction of discourse properties in the syntax of small clauses from a cross-linguistic perspective. In line with Chomsky’s (2007, 2008) idea that phasal properties should be extended to all phases, we argue for a strict parallelism between C-T and v-V, suggesting that v enters the derivation with both agreement and discourse features. These features may be inherited by V depending on the relevant language. Building on Miyagawa (2010) and Jimenez-Fernandez (2010), we claim that in Spanish and Greek, in contrast with English, both agreement and discourse features are inherited by V. This strategy accounts for the different order rearrangements detected in small clauses. The proposal can easily be extended to other languages such as Italian, Serbo-Croatian, Russian and Ukrainian, as opposed to French, Norwegian, Afrikaans and German.